С60 fullerene inhibits the deve lopment of inflammation and alteration of hematopoiesis in experimental chronic cholangitis - Byelinska, I.V.; Kuznietsova, H.M.; Dziubenko, N.V.; Hutsaliuk, M.A.; Rybalchenko, T.V.; Prylutska, S.V.; Rybalchenko, V.K. (Reports of the National Academy of Sciences of Ukraine, 2019)
The effect of C60 fullerene on the state of blood cells under experimental chronic cholangitis is studied. Intraperitoneal administration of C60 fullerene inhibits the development of inflammation, which is confirmed by a decrease in the content of eosinophilic granulocytes and lymphocytes, involves neutrophil granulocytes in the C60 accumulation, causing neutrophilia in blood, and enhances the manifestations of anemia. Oral application of C60 inhibits the development of inflammation without increasing the number of neutrophilic granulocytes in blood and partly reduces the manifestations of anemia by maintaining the amount of erythrocytes in blood, suggesting its less toxicity.